2014
DOI: 10.3892/ol.2014.2192
|View full text |Cite
|
Sign up to set email alerts
|

DNA repair gene XRCC3 Thr241Met polymorphism and susceptibility to glioma: A case-control study

Abstract: The DNA repair gene, X-ray repair cross-complementing group 3 (XRCC3) Thr241Met polymorphism may be associated with a susceptibility to glioma. The present study aimed to investigate the association between the XRCC3 Thr241Met polymorphism and the potential susceptibility to gliomas. A hospital-based case-control study was conducted, which included a total of 886 patients with glioma and 886 healthy control subjects. Peripheral blood samples were extracted and the polymerase chain reaction-restriction fragment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
(30 reference statements)
0
5
0
Order By: Relevance
“…A number of recent studies have indicated that gene polymorphism is closely associated with risk of glioma formation. Xu et al (2014) showed that the X-ray repair cross complementing group 3 gene (XRCC3) Thr241Met polymorphism increases glioma susceptibility, as its frequency is significantly higher in glioma patients as compared with the control subjects. Retinoblastoma binding protein 6 gene variants were also reported to be associated with glioma, and contribute to glioma susceptibility (Hu et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…A number of recent studies have indicated that gene polymorphism is closely associated with risk of glioma formation. Xu et al (2014) showed that the X-ray repair cross complementing group 3 gene (XRCC3) Thr241Met polymorphism increases glioma susceptibility, as its frequency is significantly higher in glioma patients as compared with the control subjects. Retinoblastoma binding protein 6 gene variants were also reported to be associated with glioma, and contribute to glioma susceptibility (Hu et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The final 14 eligible studies included a total of 12,905 study participants, including 5,852 cases and 7,053 controls (Table 1). Eight (8) of these 14 studies were conducted in China, with subjects from the Asian population [28,33,37,39,40,[42][43][44]; the other seven studies were predominantly Caucasian-with three studies from the United States [21,24,36] and one each from Spain [41] and Brazil [34], and one study from multiple countries [18]. In addition, 11 studies used hospital-based controls [21,24,33,36,37,[39][40][41][42][43][44], whereas the remaining 3 studies opted for population-based controls [18,34,36].…”
Section: Characteristics Of the Studiesmentioning
confidence: 99%
“…Eight (8) of these 14 studies were conducted in China, with subjects from the Asian population [28,33,37,39,40,[42][43][44]; the other seven studies were predominantly Caucasian-with three studies from the United States [21,24,36] and one each from Spain [41] and Brazil [34], and one study from multiple countries [18]. In addition, 11 studies used hospital-based controls [21,24,33,36,37,[39][40][41][42][43][44], whereas the remaining 3 studies opted for population-based controls [18,34,36]. In addition, all studies except Liu et al [36] reported the frequencies of the three genotypes (Thr/Thr, Thr/Met, and Met/Met) separately.…”
Section: Characteristics Of the Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…This polymorphism is mentioned as Thr241Met. Several studies have evaluated the association between Thr241Met polymorphisms and GC susceptibility (17,(19)(20)(21). There are controversies and diversities in the effect of Thr241Met polymorphism on GC, especially in Asian countries.…”
Section: Introductionmentioning
confidence: 99%